Wielowymiarowe skalowanie preferencji z wykorzystaniem modelu PREFSCAL - Zaborski, Artur (Multidimensional Preferences Scaling with the Use of PREFSCAL Model, 2009)
Unfolding analysis is a special case of multidimensional scaling. It assumes that different individuals perceive various objects of choice in the same space, but differ with respect to what they consider an ideal combination of the objects' attributes. The article presents PREFSCAL algorithm in which avoiding degeneracy in multidimensional unfolding is possible by modification of the loss function. Finally, empirical data set was analyzed by PREFSCAL method to show the benefits of the modification of the loss function.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 114-123